(3RgQ GdQHjY aj ThGgO GdHOjYs - (3GHf obrQrbeGS, eMeO Hf bQbeGS Hf YHO Gddg GdfGUQj,J (B882 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje ef eeO Gdchf CSJeO GdJhajb hGdYhf deG QCi SGOGJ Ydei GdeYGfi hGdHjGf bO CTGQhG Edi EjVGM eHge GdHOjY Hcd TGgO hHjGf eY CfUGQge Ydi cJH eWhdI s
(3BNQgG (B:s
(3aEf gPG GdYde gh ef Ydhe JaSjQ GdbQBf GdcQje hEdi Gddg CJhSd Yf CfRd Ydjg UhaI Mdbg GdQhDa GdQMje GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bSeI GdeDda Ydi KdGKI hCQHYjf HGHkG haQZ efg ai QeVGf SfI (B862(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B10 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B150s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B959s
Keywords: (3GddZIs